Synthesis and properties of 5-(((5-amino-1,3,4-thiadiazole-2-yl)thio) methyl)-4-phenyl-1,2,4-triazole-3-thione and its some S-derivatives - Hotsulia, А. S.; Fedotov, S. O.; Гоцуля, Андрій Сергійович; Федотов, С. О.; Гоцуля, А. С. (Запорізький державний медичний університет, 2020)
Increased attention to thiadiazole and 1,2,4-triazole derivatives is determined by the extensive structural modification capabilities of heterocyclic system derivatives and their high pharmacological potential. Synthesis of new molecules containing, along with the 1,2,4-triazole moiety, thiadiazole is a promising trend in the field of biologically active substances. The aim of this work was to study the reaction of nucleophilic substitution of 5-((5-amino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole- 3-thione with haloalkanes and to establish the structure of the obtained compounds. Materials and methods. Thiosemicarbazide was used as the key starting reagent. As a result of the reaction of the starting material with carbon disulfide in dimethylformamide, a thione was obtained which was further reacted with the iso-propyl ester of the chloroethane acid. The resulting ester was used for further transformations using hydrazinolysis reaction, nucleophilic addition, and intramolecular alkaline heterocyclization. The alkylderivatives of the obtained 5-((5-amino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4- triazole-3-thione were synthesized by reaction with bromoalkanes, in an alcohol medium with an equimolecular amount of alkali. The structure of the synthesized compounds was confirmed by modern physical-chemical methods of analysis: 1H NMR spectroscopy, IR spectrophotometry, and elemental analysis data. The individuality of substances was established by means of high-performance liquid chromatography. Results. The method of obtaining 5-((5-amino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thione has been optimized. The optimal conditions for the synthesis S-alkylderivatives of 5-((5-amino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thione were determined. The structure of the synthesized compounds was established and their physical properties were investigated. Conclusions. A number of S-alkylderivatives of 5-((5-amino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thione were obtained and their structure was confirmed by modern physical-chemical methods of analysis. Увага до похідних тіадіазолу та 1,2,4-тріазолу зумовлена широкими можливостями структурної модифікації похідних цих гетероциклічних систем та їхнім високим фармакологічним потенціалом. Синтез нових молекул, що містять тіадіазол поряд із фрагментом 1,2,4-тріазолу, – перспективний напрям у галузі створення біологічно активних субстанцій. Мета роботи – вивчення реакції нуклеофільного заміщення 5-((5-аміно-1,3,4-тіадіазол-2-ілтіо)метил)-1,2,4-тріазол-3-тіону за участю галогеналканів і встановлення структури одержаних сполук. Матеріали та методи. Як ключовий вихідний реагент використали тіосемікарбазид. У результаті реакції взаємодії вихідної ре¬човини з карбон дисульфідом у середовищі диметилформаміду отримали тіон, який надалі піддали взаємодії з ізо-пропіловим естером кислоти хлоретанової. Естер, що одержали, застосували для наступних перетворень, використовуючи реакції гідразинолізу, нуклеофільного приєднання та внутрішньомолекулярної лужної гетероциклізації. Алкілпохідні 5-((5-аміно-1,3,4-тіадіазол- 2-ілтіо)метил)-1,2,4-тріазол-3-тіону синтезовані взаємодією з бромоалканами за наявності еквімолекулярної кількості лугу у спиртовому середовищі. Структура синтезованих сполук підтверджена за допомогою сучасних фізико-хімічних методів аналізу: 1Н ЯМР спектроскопії, ІЧ-спектрофотометрії та даними елементного аналізу. Індивідуальність речовин встановлена за допомогою високоефективної рідинної хроматографії. Результати. Оптимізували методику одержання 5-((5-аміно-1,3,4-тіадіазол-2-ілтіо)метил)-1,2,4-тріазол-3-тіона. Визначили оптимальні умови синтезу S-алкілпохідних 5-((5-аміно-1,3,4-тіадіазол-2-ілтіо)метил)-1,2,4-тріазол-3-тіону, встановили будову синтезованих сполук і дослідили їхні фізичні властивості. Висновки. Отримали ряд S-алкілпохідних 5-((5-аміно-1,3,4-тіадіазол-2-ілтіо)метил)-1,2,4-тріазол-3-тіону, структуру яких підтвердили за допомогою сучасниx фізико-хімічних методів аналізу. Повышенное внимание к производным тиадиазола и 1,2,4-триазола определяется широкими возможностями структурной модификации производных этих гетероциклических систем и их высоким фармакологическим потенциалом. Синтез новых молекул, содержащих тиадиазол наряду с фрагментом 1,2,4-триазола, – перспективное направление в области создания биологически активных субстанций. Цель работы – изучение реакции нуклеофильного замещения 5-((5-амино-1,3,4-тиадиазол-2-илтио)метил)-1,2,4-триазол-3-тиона при участии галогеналканов, а также установление структуры полученных соединений. Материалы и методы. В качестве ключевого исходного реагента использован тиосемикарбазид. В результате реакции взаимодействия исходного вещества с карбон дисульфидом в среде диметилформамида получен тион, который подвергали взаимодействию с изо-пропиловым эфиром кислоты хлорэтановой. Полученный эфир использован для дальнейших преобразований с использованием реакций гидразинолиза, нуклеофильного присоединения и внутримолекулярной щелочной гетероциклизации. Алкилпроизводные полученного 5-((5-амино-1,3,4-тиадиазол-2-илтио)метил)-1,2,4-триазол-3-тиона синтезированы взаимодействием с бромалканами в присутствии эквимолекулярного количества щелочи в спиртовой среде. Структура синтезированных соединений подтверждена с помощью современных физико-химических методов анализа: 1Н ЯМР спектроскопии, ИК-спектрофотометрии и данными элементного анализа. Индивидуальность веществ установлена с помощью высокоэффективной жидкостной хроматографии. Результаты. Оптимизирована методика получения 5-((5-амино-1,3,4-тиадиазол-2-илтио)метил)-1,2,4-триазол-3-тиона. Определены оптимальные условия синтеза S-алкилпроизводных 5-((5-амино-1,3,4-тиадиазол-2-илтио)метил)-1,2,4-триазол-3-тиона, установлено строение синтезированных соединений и исследованы их физические свойства. Выводы. Получен ряд S-алкилпроизводных 5-((5-амино-1,3,4-тиадиазол-2-илтио)метил)-1,2,4-триазол-3-тиона, структура которых подтверждена с помощью современных физико-химических методов анализа.
Синтез і властивості 5-(((5-аміно-1,3,4-тіадіазол-2-іл)тіо)метил)-4-феніл-1,2,4-тріазол-3-тіону та його деяких S-похідних
Синтез и свойства 5-(((5-амино-1,3,4-тиадиазол-2-ил)тио)метил)-4-фенил-1,2,4-триазол-3-тиона и его некоторых S-производных
Keywords: 5-aminothiadiazole; 1,2,4-triazole; physical-chemical properties; 5-амінотіадіазол; 1,2,4-тріазол; фізико-хімічні властивості; 5-аминотиадиазол; 1,2,4-триазол; физико-химические свойства